Amylose and amylopectin in selected Malaysian foods and its relationship to glycemic index - Nik Shanita .S; Hasnah .H; Khoo .C.W (Universiti Kebangsaan Malaysia, 2011)
The aim of this study was to determine the nutrient contents and to evaluate the relationship between amylose and amylopectin content to glycemic index of diet commonly eaten by Malaysian. The food samples consisted of nasi lemak, fried rice, fried rice noodle, fried macaroni, sandwich sardine, doughnut, curry puff and roti canai with dhal. Each sample was prepared based on standard recipe (except doughnut, roti canai with dhal and curry puff were bought from 3 different locations) in two different cycles. Moisture, ash, crude protein and crude fat were analyzed using proximate analysis whereas amount of carbohydrate was calculated “by difference”. Total dietary fiber was analyzed using AOAC 991.43. The content of amylose and amylopectin were analyzed using colorimetric method and calculated “by difference”, respectively. Our results showed that doughnut contained the highest carbohydrate (49.49 ± 1.24 g/100 g) while nasi lemak had the lowest carbohydrate (25.04 ± 0.56 g/100 g). Roti canai with dhal had the highest total dietary fiber content (3.89 ± 0.43 g/100 g). The highest amylose content was found in roti canai with dhal (11.75 ± 1.38%) while highest amylopectin content was in nasi lemak (94.19 ± 0.48%). The amylose content of tested samples ranged from 5 to 12%. In conclusion, results showed that there was no significant relationship between the ratio of amylose to amylopectin and glycemic index but negative trend existed which indicated increase in amylose content will lower the glycemic index of a food.